Mitochondrial DNA variant spectrum and the association with chronic tic disorders. (20th July 2022) - Jiang, Peifang; Zhu, Tao; Liu, Jiajing; Tao, Xiaohan; Xue, Ziru; Tao, Yiling; Chen, Hongyu; Zeng, Xiaojing; Zhu, Weiyi; Shu, Qiang; Yu, Lan
Abstract: Background and purpose: Tic disorders (TDs) are childhood onset neuropsychiatric disorders characterized by single or multiple sudden, rapid, recurrent, and motor tics and/or vocal tics. Several nuclear genes that are involved in mitochondrial functions suggest a potential role of mitochondria in TDs. Methods: To evaluate the association of mitochondrial DNA (mtDNA) variants with TDs, we screened the whole mitochondrial genomes in 493 TD patients and 109 age‐ and sex‐matched healthy controls using next generation sequencing technology. Results: A total of 1918 mtDNA variants including 1220 variants in patients only, 154 variants in controls only, and 544 variants shared by both cases and controls were identified. We found a higher number of overall mtDNA variants in TD patients ( p  = 0.00028). The variant density in MT‐ATP6/8 and MT‐CYB coding regions showed a significant difference between TD patients and controls ( p  = 0.0025 and p  = 0.003, respectively). Furthermore, we observed a significant association of 15 common variants with TD based on an additive model, including m.14766C > T, m.14783 T > C, m.14905G > A, and m.15301G > A in MT‐CYB ; m.4769A > G, m.10398A > G, m.12705C > T, and m.12850A > G in MT‐ND genes; m.7028C > T in MT‐CO1 ; m.8701A > G in MT‐ATP6 ; two variants with m.16223C > T, m.5580 T > C in noncoding regions; and three rRNA variants with m.1438A > G and m.750A > G in RNR1, and m.2352 T > C in RNR2 . Conclusions: Our data provide evidence of mtDNA variants associated with TDs. The accumulation of the heteroplasmic levels may increase the risk of TDs. Replication studies with larger samples are necessary to understand the pathogenesis of TDs. Abstract : A total of 1918 mitochondrial DNA (mtDNA) variants were identified in the cohort of 491 patients with chronic tic disorders (TDs) and 109 controls. Overall, TD patients carried a significantly higher number of mtDNA variants than controls. Specifically, a number of common variants in coding the genes ATP6 and MT‐CYB and noncoding regions were found to be associated with TD based on an additive model.